Brazilian postgraduate programs in Food and Nutrition: Considerations on evaluation procedures - Pacheco da Costa PROENÇA, Rossana; Donizete PRADO, Shirley; AMPARO-SANTOS, Ligia; RETONDARIO, Anabelle; de Andrade ALVES, Juliede; de Carvalho Sampaio de SOUZA, Liv Katyuska (Revista de Nutrição, 2023)
This essay aims to present some considerations on the development of research and teaching skills, intellectual production, and current situation of stricto sensu postgraduate programs in Food and Nutrition, particularly of professional and academic master’s and doctoral programs currently classifi ed in the evaluation category Nutrition by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior. The elements of evaluation procedures are discussed, as are the scores given to the programs in the most recent Coordenação de Aperfeiçoamento de Pessoal de Nível Superior report. There was a marked increase in the participation of Food and Nutrition postgraduate programs in the national context. Many challenges still need to be overcome, such as the offer of Nutrition postgraduate programs in the Northeast region and outside the capital cities of the country. Evaluation criteria and procedures need to be better developed to consider the main characteristic of the scientific field of Food and Nutrition, its multiplicity of disciplines.